2008
DOI: 10.1093/nar/gkn964
|View full text |Cite
|
Sign up to set email alerts
|

Physical and functional interaction between DDB and XPA in nucleotide excision repair

Abstract: Damaged DNA-binding protein (DDB), consisting of DDB1 and DDB2 subunits recognizes a wide spectrum of DNA lesions. DDB is dispensable for in vitro nucleotide excision repair (NER) reaction, but stimulates this reaction especially for cyclobutane pyrimidine dimer (CPD). Here we show that DDB directly interacts with XPA, one of core NER factors, mainly through DDB2 subunit and the amino-acid residues between 185 and 226 in XPA are important for the interaction. Interestingly, the point mutation causing the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…Recent reports have identified that the N terminus of DDB2 is also PARylated in vivo in response to UV damage, resulting in stabilization of UV-DDB on damaged chromatin (50,51). How posttranslational modifications such as phosphorylation (52), SUMOylation (53), ubiquitylation (21), and PARylation (50, 51), as well as interacting partners such as XPC and XPA (21,54,55), may regulate the dimerization and lifetimes of the kinetic intermediates identified in this work need to be further investigated.…”
Section: Conformational Proofreading Is a Candidate Mechanism For Damagementioning
confidence: 99%
“…Recent reports have identified that the N terminus of DDB2 is also PARylated in vivo in response to UV damage, resulting in stabilization of UV-DDB on damaged chromatin (50,51). How posttranslational modifications such as phosphorylation (52), SUMOylation (53), ubiquitylation (21), and PARylation (50, 51), as well as interacting partners such as XPC and XPA (21,54,55), may regulate the dimerization and lifetimes of the kinetic intermediates identified in this work need to be further investigated.…”
Section: Conformational Proofreading Is a Candidate Mechanism For Damagementioning
confidence: 99%
“…Surprisingly, however, relatively few cellular proteins have been shown to date to be regulated by these complexes. CRL4A (DDB2) promotes the ubiquitination of histones 2A, 3, and 4 (28,53); of xeroderma pigmentosum group C protein (XPC) (48); and probably of xeroderma pigmentosum group A protein (XPA) (52) to facilitate UV damage repair. CRL4A (CSA) and CRL4A (DET1-COP1) induce the proteolysis of Cockayne syndrome type B gene product (CSB) (18) and c-JUN (56), respectively.…”
mentioning
confidence: 99%
“…The DDB complex can bind damaged DNA independently of XPC or any other core components of NER [113], suggesting that it is the first recognition protein to reach the UV-damage site and then help to recruit XPC-HR23 to the lesion, followed by the recruitment of XPA for lesion verification, triggering the NER process [114,115]. Support for the above notion includes observations that the tertiary complex of DDB1, DDB2, and XPA is assembled at the damaged DNA site in the early stage of NER [116]. Although (6-4) PPs can also be recognized by XPC, the relocation of XPC to CPDs requires the presence of functional DDB2 [114].…”
Section: Uv-ddb Heterodimer Forms E3s and Regulates Ner Efficiencymentioning
confidence: 95%